Potting media made with bokashi compost to improve the growth and biomass accumulation of rubber seedlings - Gashua, Auwalu Garba; Sulaiman, Zulkefly; Mohammad Yusoff, Martini; Abd Samad, Mohd Yusoff; Ramlan, Mohd Fauzi; Salisu, Monsuru Adekunle; Mokhatar, Mohd Shafar Jefri (Springer, 2022)
Lack of good potting media to produce good planting materials for rubber plantations is one of the problems affecting natural rubber (NR) growers and this demands viable solutions. This work describes the effects of potting media made with horse waste-based bokashi compost on the growth and biomass accumulation of rubber seedlings. The research involved four potting media (M1 = 1:0 soil:bokashi, M2 = 1:1 soil:bokashi, M3 = 2:1 soil:bokashi, and M4 = 1:2 soil:bokashi), as well as PB 350 and RRIM 2002 seedlings. Growth parameters assessed were plant height and girth size per plant. Shoot and root dry weights were computed to evaluate the biomass accumulation using indices such as the relative growth rate (RGR), net assimilation rate (NAR), leaf area ratio (LAR), specific leaf area (SLA), root–shoot ratio (RSR) and leaf weight ratio (LWR). Significant growth in terms of plant height was achieved in M4 with the tallest plants (114.1 cm) compared to 93.1 cm in M1 (corresponding to 74.4 and 42.0% height increment, respectively). Plant height increased by 66.3% in RRIM 2002 as compared to 54.6% in PB350. Also, M4 provided a significant shoot dry weight of 139.0 g/plant, leaf area of 4233.2 cm2/plant compared to 58.1 g/plant and 1832.3 cm2/plant, respectively, in the control-M1. Interaction results indicated that RRIM 2002 clone provided the highest RGR (0.011 g/g/day) in M4. This work also demonstrated that adding bokashi to the soil significantly improved most of the chemical properties (but did not significantly change the physical properties) with RRIM 2002 clone responding better to bokashi potting media compared to PB 350 clone.